Assessing the effectiveness of governance innovations: A comparative study of ten European cities - Nowicka, Klaudia; Sagan, Iwona; Grabkowska, Maja; Tokarek, Agata; Wielgórska, Monika (Bulletin of Geography. Socio-economic Series, 2026)
The aim of this study is to investigate the effectiveness of governance innovations in enhancing deliberative and participatory democracy across ten European cities. The research, conducted under the EUARENAS Project and funded by the European Union’s Horizon 2020 programme, explores the impact of various participatory and deliberative methods in diverse socio-political contexts. Utilizing a case study approach, the analysis includes eleven governance innovations from cities in both Western and Central-Eastern Europe, reflecting a wide array of tools and strategies aimed at improving citizen engagement and local democracy. The findings highlight the contextual factors influencing the success of these methods, emphasizing the importance of cultural, social, and historical nuances. ...